Crime scene investigation involving the Expert Service of the Ministry of Internal Affairs and the Police: Selected issues - Volodymyr ATAMANCHUK,; Oleh KRAVCHUK,; Yurii CHECHIL,; Lesia TALIANCHUK,; Vasyl HOLOBOTOVSKYI, (Revista Jurídica Portucalense, 2023)
The purpose of study is to establish the main features in the interaction and joint participation of specialists of the National Police of Ukraine and the Expert Service of the Ministry of internal affairs of Ukraine in the implementation of an inspection of the scene of an illegal act, as well as determining the real state of their functioning and problems that arise during such interaction. Among the methods used to study this topic are dialectical method, formalisation method, law-recognising method, formal-legal method, and others. The results of this article are the definition and establishment of the characteristics and features of interaction and joint participation of the National Police of Ukraine and the Expert Service of Ukraine during the inspection of the scene of the committed crime; characterised the units of the Expert Service that are involved in the implementation of the inspection of the scene of the committed criminal act.